2011
DOI: 10.1371/journal.pone.0019881
|View full text |Cite
|
Sign up to set email alerts
|

What Is New for an Old Molecule? Systematic Review and Recommendations on the Use of Resveratrol

Abstract: BackgroundResveratrol is a natural compound suggested to have beneficial health effects. However, people are consuming resveratrol for this reason without having the adequate scientific evidence for its effects in humans. Therefore, scientific valid recommendations concerning the human intake of resveratrol based on available published scientific data are necessary. Such recommendations were formulated after the Resveratrol 2010 conference, held in September 2010 in Helsingør, Denmark.MethodologyLiterature sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
343
1
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 398 publications
(355 citation statements)
references
References 142 publications
(143 reference statements)
4
343
1
7
Order By: Relevance
“…This suggests that marked benefits may accrue from use of tRES-HESP coformulation. Safety assessments of tRES and HESP indicate that they are highly tolerated (19,20). Studies of human BJ fibroblasts in primary culture showed no toxicity of tRES and HESP individually or with 5 mmol/L combination with primary bioactive compound at concentrations #20 mmol/L.…”
Section: Diabetesdiabetesjournalsorgmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that marked benefits may accrue from use of tRES-HESP coformulation. Safety assessments of tRES and HESP indicate that they are highly tolerated (19,20). Studies of human BJ fibroblasts in primary culture showed no toxicity of tRES and HESP individually or with 5 mmol/L combination with primary bioactive compound at concentrations #20 mmol/L.…”
Section: Diabetesdiabetesjournalsorgmentioning
confidence: 99%
“…We limited the small-molecule inducer screen to nontoxic dietary bioactive compounds of known or suspected Nrf2 activation activity to provide an option for use of Glo1 inducers as functional food supplements as well as pharmaceuticals. tRES and HESP also have a .50-fold safety margin at doses used in the HATFF study (19,20). Activation of Nrf2 by dietary bioactive compounds is mostly studied through ARE-linked induction of NQO1 or HMOX1 expression.…”
Section: (232%) [-]mentioning
confidence: 99%
“…A full discussion of these issues is beyond the scope of this review, and has been attempted elsewhere (e.g. [21][22][23]). The complexity of resveratrol's effects in cells and in animals presents a major challenge in moving forward with human studies.…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol has shown evidence of decreasing cancer incidence, heart disease, metabolic syndrome and neural degeneration in animal studies [7]. As human clinical trials of resveratrol are now underway [7], it is high time to review the current state of knowledge regarding the life-extending properties of resveratrol. To our knowledge, this is the first quantitative review of resveratrol using rigorous meta-analytic methods.…”
Section: Introductionmentioning
confidence: 99%